Persistence of Neonatal Brachial Plexus Palsy Associated with Maternally Reported Route of Delivery: Review of 387 Cases - Chang, Kate W.-C.; Ankumah, Nana-Ama E.; Wilson, Thomas J.; Yang, Lynda J.-S.; Chauhan, Suneet P. (American Journal of Perinatology, 2016)
Objective The factors associated with persistent neonatal brachial plexus palsy (PNBPP) are unknown. Our objectives are to compare PNBPP at 1 and 2 years in children delivered via vaginal delivery (VD) versus cesarean delivery (CD) and in children delivered via VD with or without reported shoulder dystocia (SD).Study Design Retrospective cohort of children diagnosed with neonatal brachial plexus palsy (NBPP). Maternally reported delivery history and presence of SD were recorded with Student t-test, chi-square test, and odds ratio (OR) with 95% confidence intervals (CI) calculated for comparisons.Results Of 387 cases of NBPP, 8% (30) delivered via CD. Rates of PNBPP were higher in the VD group at 1 and 2 years (60% of CD and 85% of VD; OR, 0.26; 95% CI, 0.11–0.62 at 1 year; 33% of CD and 73% of VD; OR, 0.15; 95% CI, 0.05–0.39 at 2 years). There was no difference in PNBPP in women with VD with or without maternally reported SD (87 vs. 85%, p = 0.68 at 1 year; 64 vs. 61%, p = 0.61 at 2 years).Conclusion PNBPP is possible with CD, and there is no difference in PNBPP in VD with or without maternally reported SD. A prospective study is warranted to ascertain associative factors.
Keywords: neonatal brachial plexus palsy; shoulder dystocia; persistent; vaginal delivery; cesarean delivery